The Public Signs of Vilnius: Languages and Genres - Daraškienė, Inga (Lietuvių kalba, 2024)
This article introduces the results of Vilnius’s linguistic landscape research. The analysis focuses on which signs make up the linguistic landscape of Vilnius and which languages are used on the signage. The study material consists of 2,442 public and private signs collected from various neighborhoods in Vilnius in 2020, March-October. The research employs quantitative statistical descriptive analysis and qualitative content analysis. The data shows that 76% of all signs include Lithuanian: 49% are monolingual Lithuanian, and 27% are multilingual with Lithuanian. The remaining 24% of signs use other foreign languages. Lithuanian is used in all types of signs, and the only monolingual Lithuanian signs are road signs and street names, apart from decorative plaques with foreign languages on them. Lithuanian is the first language in most multilingual signs, followed by other foreign languages. This language pattern is usually seen on commercial establishments or public institution signage, such as opening hours or services provided. Multilingual signs where Lithuanian is not the first language account for 8.3% of all Vilnius signs analyzed in this study. English-Lithuanian is the most frequent language pattern in these signs. If Lithuanian is not the first language used on a sign, the most common language model is English-Lithuanian, and mostly bilingual English-Lithuanian signs are names of establishments. Research shows that the first foreign language used in a sign does not always play a stronger communicative function, as it may be used because of its symbolic power. The analysis of monolingual signs in foreign languages shows that the most significant proportion of such signs are stickers, shop signs, and graffiti, and the most common languages are English, Russian, Italian, German, French, Latin, and Latin.